THE EFFECTIVENESS OF THE LEARNING CLASSES CATEGORIZATION BASED ON STUDENTS’ EDUCATIONAL BACKGROUND IN MASTERING ARABIC - Zubaidah Zubaidah (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2020)
This research aimed to know the effectiveness of the division learning classes based on students’ educational background in Arabic at IAIN Bukittinggi. This research was a quantitative research. The population of this research was the Arabic Students of 2019/2020 who have undergone grouping system based on the school background in Arabic classes. The data was collected by online questionnaire on 75 students and 7 lecturers and was analyzed with Likert scale. The results showed that majority of students agreed with the grouping system because it helped them to improve their Arabic, to be more confident during the lesson, and to understand the given materials according to their learning outcomes. The data analysis also showed that the grouping system could measure students' abilities and increase students’ competitiveness in the process. Meanwhile, a small number of students expressed their disapproval of the grouping system because it limited their Arabic ability in order to have the proper chance to discuss the given materials with those who have previously learned Arabic.